Participatory Communication in the Gender Equality Awareness Program 'Cerita Bunda' haibunda.com - Iin Yumiyanti*; Ana kuswanti; Munadhil Abdul Muqsith (Universitas Syiah Kuala, 2024)
Gender inequality in Indonesia is very high and even in 2021, it was the highest in ASEAN. BPS data, in the following years there was a decrease in the gender inequality index, but the decrease was not significant, and it turned out that complaints of cases of violence against women increased. According to Komnas Perempuan, in 2023, the number of complaints of cases of violence against women was 4,374 cases, an increase compared to the previous year. Law Number 40 of 1999 concerning the Press requires the mass media to assist in efforts to increase gender equality. Fulfilling this obligation, Haibunda.com as a mass media created the